The Full Circle: Transmission of Ideas & the Muslim Social Scientist (American Journal of Islam and Society, 2001)
Science Without Philosophy?Many of our readers and contributors have raised questions regarding thevarious definitions of social science and their relation to the scope of MISS.Definitions of social science have changed with time and place, and one of thereasons for that is not what is “social,” but what is “science”? “Science” inFrench, or “wissenschaft” in German, do not translate exactly the same as“science” in English. In English speaking world, “science” has an associationwith hard sciences while social sciences have been tacitly considered to be softsciences, or not sciences at all. Such a distinction does not exist in otherlanguages.It is not our intent here to provide a mere taxonomy of the meanings ofscience, but to develop an understanding as well as a consensus that socialsciences and their sub-disciplines are, without exception, based on certainparadigms that are philosophical in nature. Being a social scientist without theknowledge of these philosophical assumptions, upon which the paradigms ofthe socia1 sciences rest, is to willingly escape the full picture. Properphilosophical training, therefore, has a deep nexus with the methods of socialscience, and constitutes a necessary pre-requisite of understanding theparadigms. Paradigms establish the agenda and the agenda dictates the policy.social sciences therefore become a vehicle of understanding the society inconsonance with the accepted philosophical truths.Philosophical exposition of concepts and ideas in turn necessitates adefinition of philosophy itself. All definitions of philosophy will point tocertain “givens” or a priori assumptions that precede all scientific inquiry. Ifsocial sciences stay within the realm of the positivist paradigm, the problemmay seemingly be solved, but reducing inquiry to empiricism has its own pitfallsand the atomistic division in today’s academia is a direct result of that.Further, it restricts the scope of those social scientists who also happen to bebelievers in transcendental Truth. Conversely, to the degree that philosophy is ...